Recurrent infections and immunodeficiency in a patient with Sanfilippo syndrome (MPS type 3) - Özdemir, Öner; Tokmak, Kübra (Alergologia Polska - Polish Journal of Allergology, 2026)
Sanfilippo syndrome (mucopolysaccharidosis type III, MPS III) is a rare lysosomal storage disorder characterized by progressive neurodegeneration, behavioral abnormalities, and multisystemic involvement, with autosomal recessive inheritance. Recent findings suggest that immune system disorders may play a role in the pathogenesis and clinical complications of the disease, in addition to the classic neurological presentation. In this case, total IgG and subclass deficiencies were detected in an 18-year-old female patient who was being monitored for frequent respiratory tract infections, and intravenous immunoglobulin (IVIG) treatment was initiated with a diagnosis of humoral immunodeficiency. A significant decrease in the incidence of post-treatment infections and hospital admissions has been observed. Immune system involvement in MPS patients may increase the risk of infection. Therefore, immunological evaluation and appropriate treatment approaches are critical for improving quality of life.